Agreement between the BRAC University-Institute of Educational Development and Open Society Foundation for Cooperation on a Professional Development Program on Early Childhood Development (2006) - BRAC University-Institute of Educational Development (BU-IED); Open Society Foundation (Institute of Educational Development, BRAC University and Open Society Foundation, 2013)
This Agreement is signed between the BRAC University of Educational Development having its office at House 113, Road 2, Block A, Gulshan 1, Dhaka-1212, Bangladesh represented by its Director Dr. Manzoor Ahmed, hereinafter referred to as BU-IED and Open Society Foundation having its office at Cambridge House, 100 Cambridge Grove, London W6 OLE, United Kingdom represented by Dr. W. H. Newton-Smith hereinafter referred to as OSF.